Development Strategy of Sago Local Food Agroindustry Using Analytical Hierarchy Process Method - Timisela, Natelda Rosaldiah; Masyhuri, Masyhuri; Darwanto, Dwidjono Hadi (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to formulate the development strategy for sago local food agroindustry in Maluku Province. The sample was taken deliberately (purposive sampling) because respondents realize the sago development in the province. The respondents, totaling 15 people, consisted of farmers, traders, and experts from several agencies, namely the Food Security Agency, the Department of Agriculture, the Department of Industry and Commerce, the Department of Cooperatives and Small and Medium Micro Enterprises, Universities, and Non-Governmental Organizations. Data analysis utilized the Analytic Hierarchy Process method. The priority analysis results of sago agroindustry development strategy revealed technology as a top priority in the agroindustry development for being associated with very low and limited assistance and access to processing technology. The sago local food agroindustry development focuses on linkages between factors, sub-factors, actors, objectives, and policy scenarios. The recommended policy scenarios are preserving local food, improving technology, arranging marketing strategies, improving production facilities and infrastructure, and improving institutional systems.